A compact ultrathin broadband absorber by reducing cross‐polarized reflection from metal‐backed anisotropic array. Issue 4 (April 2017) - Kundu, Debidas; Mohan, Akhilesh; Chakrabarty, Ajay
ABSTRACT: In this article, cross‐polarized reflection from a periodic array of metal‐backed anisotropic units is reduced in order to achieve a compact ultrathin absorber. Using a frequency selective surface (FSS) as middle layer (ML), the peak absorptivity is improved from 23.75% to 73.45%, while its thickness and full width at half maxima (FWHM) bandwidth is kept unaltered. The absorption characteristics of the array of anisotropic units without and with ML are investigated in details. The proposed array with ML provides FWHM absorption bandwidth of 24% (2.73–3.45 GHz), while it has thickness and periodicity of only λ / 30 and λ / 4, respectively, with respect to the mid operating frequency (3.15 GHz). Measurement results show good agreement with the numerically simulated results. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:970–976, 2017